Prospects for determining the mass distributions of galaxy clusters on large scales using weak gravitational lensing. Issue 4 (21st May 2018) - Fong, M; Bowyer, R; Whitehead, A; Lee, B; King, L; Applegate, D; McCarthy, I
ABSTRACT: For more than two decades, the Navarro, Frenk, and White (NFW) model has stood the test of time; it has been used to describe the distribution of mass in galaxy clusters out to their outskirts. Stacked weak-lensing measurements of clusters are now revealing the distribution of mass out to and beyond their virial radii, where the NFW model is no longer applicable. In this study, we assess how well the parametrized Diemer & Kravstov (DK ) density profile describes the characteristic mass distribution of galaxy clusters extracted from cosmological simulations. This is determined from stacked synthetic lensing measurements of the 50 most massive clusters extracted from the Cosmo-OWLS (OverWhelmingly Large Simulations), using the dark-matter-only run and also the run that most closely matches observations. The characteristics of the data reflect the Weighing the Giants survey and data from the future Large Synoptic Survey Telescope (LSST). In comparison with the NFW model, the DK model favoured by the stacked data, in particular for the future LSST data, where the number density of background galaxies is higher. The DK profile depends on the accretion history of clusters which is specified in this study. Eventually, however subsamples of galaxy clusters with qualities indicative of disparate accretion histories could be studied.